2022
DOI: 10.1152/ajpheart.00276.2022
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arteriolar and neurovascular dysfunction after chemically induced menopause in mice

Abstract: Cognitive decline is linked to decreased cerebral blood flow, particularly in women after menopause. Impaired cerebrovascular function precedes the onset of dementia, possibly due to reduced functional dilation in parenchymal arterioles. These vessels are bottlenecks of the cerebral microcirculation, and dysfunction can limit functional hyperemia in the brain. Large conductance Ca2+-activated K+ channels (BKCa) are the final effectors of several pathways responsible for functional hyperemia, and their expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 94 publications
3
13
0
Order By: Relevance
“…Further, both females and males 5x-FAD mice showed a reduction in neurovascular responses during somatosensory stimulation. A similar neurovascular impairment was recently reported by us, in which female mice that underwent chemically-induced menopause showed reduced functional hyperemia responses associated with cerebral microvascular BK Ca impairment 41 . However, it is important to note that these studies, and our data presented herein, are associative, and further experiments are needed to definitively show the role of cerebral microvascular BK Ca in neurovascular coupling responses.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Further, both females and males 5x-FAD mice showed a reduction in neurovascular responses during somatosensory stimulation. A similar neurovascular impairment was recently reported by us, in which female mice that underwent chemically-induced menopause showed reduced functional hyperemia responses associated with cerebral microvascular BK Ca impairment 41 . However, it is important to note that these studies, and our data presented herein, are associative, and further experiments are needed to definitively show the role of cerebral microvascular BK Ca in neurovascular coupling responses.…”
Section: Discussionsupporting
confidence: 84%
“…Impairment in BK Ca function is associated with vascular dysfunction in various disease models, including diabetes 48,49 , hypertension 50,51 , menopause 41,52 , cigarette smoking 53 and AD 28 . One limitation of the aforementioned studies is that they were all performed in a single sex, and the vast majority in males (with the exception of studies focused on menopause).…”
Section: Discussionmentioning
confidence: 99%
“…This observation was seen at a younger age, with lower CBF observed in older age [65,66]. HRT use in early menopause has been shown to improve peripheral vascular function [67], and in a recent study, estrogen use was associated with reduced cerebral vessels' smooth muscle tone in a menopausal mouse model [68]. It is possible that a ated effect on CBF in APOE4 could in part underpin the impact on brain volume and associated improved memory, which is worthy of future investigation.…”
Section: Discussionmentioning
confidence: 93%
“…VCID alone led to impairments in spatial memory (Barnes maze) while menopause in VCID mice led to additional impairments in episodic-like memory (NOR) and activities of daily living (nest building). Others have examined cognitive effects of the accelerated ovarian failure model of menopause at baseline and have found no deficits [ 34 ]. While others have examined the cognitive effects of an OVX model of menopause, we are the first to examine the cognitive impact of this more clinically relevant menopause model on cognitive impairment in VCID.…”
Section: Discussionmentioning
confidence: 99%
“…This well characterized model leads to permanent acyclicity in rodents with few side effects [ 32 , 33 ]. Recent elegant work by Blackwell et al, using this accelerated ovarian failure model of menopause, showed that menopause impairs cerebrovascular function [ 34 ]. The effects of menopause in the context of VCID or underlying vascular pathology had yet to be examined.…”
Section: Introductionmentioning
confidence: 99%